2016
DOI: 10.1038/cr.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

WSB1 overcomes oncogene-induced senescence by targeting ATM for degradation

Abstract: Oncogene-induced senescence (OIS) or apoptosis through the DNA-damage response is an important barrier of tumorigenesis. Overcoming this barrier leads to abnormal cell proliferation, genomic instability, and cellular transformation, and finally allows cancers to develop. However, it remains unclear how the OIS barrier is overcome. Here, we show that the E3 ubiquitin ligase WD repeat and SOCS box-containing protein 1 (WSB1) plays a role in overcoming OIS. WSB1 expression in primary cells helps the bypass of OIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 81 publications
1
32
0
Order By: Relevance
“…It was found that the E3 ligase WSB1 promoted ATM ubiquitination and degradation after its activation through CDK4-mediated phosphorylation. 46 Our results establish a novel connection between CDK4/6 and ATM, which is that CDK4/6 indirectly modulates ATM levels through RPRM. We also provide another potential mechanism for the inhibition of ATM activation by CDK4/6 inhibitor Palbociclib.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It was found that the E3 ligase WSB1 promoted ATM ubiquitination and degradation after its activation through CDK4-mediated phosphorylation. 46 Our results establish a novel connection between CDK4/6 and ATM, which is that CDK4/6 indirectly modulates ATM levels through RPRM. We also provide another potential mechanism for the inhibition of ATM activation by CDK4/6 inhibitor Palbociclib.…”
Section: Discussionsupporting
confidence: 56%
“…MEFs were isolated as described previously. 46 Briefly, mouse embryos were harvested at E13 and the internal organs were removed, then the embryo bodies were digested using 0.25% trypsin-EDTA (Beyotime) for 30 min at 37 °C, and neutralized with DMEM containing 10% FBS. The tissue homogenate was then filtered through 40 μm nylon cell strainer (Falcon) and centrifuged at 1000 rpm for 5 min, and the pellets were resuspended and cultured in completed DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that mTOR signals via two distinct protein complexes termed mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) [7]. It is well known that the regulatory protein of mTOR, mainly Raptor, has a significant role in various kidney diseases [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CRL5–WSB1 has been shown to promote tumor metastasis and promote cell cycle via degrading tumor suppressors VHL, RhoGDI2, ATM, etc. ( Cao et al, 2015 ; Kim et al, 2015 , 2017 ). Therefore, the role of CRL5 E3 complexes in cancer regulation is very complicated and possibly context dependent.…”
Section: Discussionmentioning
confidence: 99%